2013
DOI: 10.1016/j.brainresbull.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant, neuroprotective and behavioral effects of organic and conventional yerba mate (Ilex paraguariensis St. Hil.) on pentylenetetrazol-induced seizures in Wistar rats

Abstract: Epilepsy, which is one of the most common neurological disorders, involves the occurrence of spontaneous and recurrent seizures that alter the performance of the brain and affect several sensory and behavioral functions. Oxidative damage has been associated with post-seizure neuronal injury, thereby increasing an individual's susceptibility to the occurrence of neurodegenerative disorders. The present study investigated the possible anticonvulsive and neuroprotective effects of organic and conventional yerba m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 58 publications
1
22
0
1
Order By: Relevance
“…It causes neuroinflammation and oxidative stress, which affects cognition. In addition, PTZ has been observed to cause amnesia in animal models (Oscós-Alvarado and de Muñoz, 1981; Pourmotabbed et al, 2011; dos Santos Branco et al, 2013). It is also known to modulate glutamate receptors.…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…It causes neuroinflammation and oxidative stress, which affects cognition. In addition, PTZ has been observed to cause amnesia in animal models (Oscós-Alvarado and de Muñoz, 1981; Pourmotabbed et al, 2011; dos Santos Branco et al, 2013). It is also known to modulate glutamate receptors.…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…Regarding crude extracts, Ilex paraguariensis extracts have demonstrated the ability to prevent memory deficits in rats (Colpo et al 2007;Santos et al 2015), and a capacity to reduce the frequency of seizures, minimizing the neuronal damage associated with their periodic occurrence (Branco Cdos et al 2013). Moreover, Cittadini et al (2015) reported that this plant could be a source of chemopreventive agents to combat oxidative stress-related neurodegenerative pathologies because of its redox effects in brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…In both organic and conventional infusions, the presence of the polyphenols rutin and chlorogenic acid and their acyl derivatives were detected (Branco Cdos et al, 2013), which could be associated with the anticonvulsant and neuroprotective effects. In both organic and conventional infusions, the presence of the polyphenols rutin and chlorogenic acid and their acyl derivatives were detected (Branco Cdos et al, 2013), which could be associated with the anticonvulsant and neuroprotective effects.…”
Section: Effects On Nervous Systemmentioning
confidence: 99%